Adaptive Governance as Strategic Management: Integrating Local Knowledge, Institutional Flexibility, and Social Capital in Socio-Ecological Resilience - Anggriani, Nina; Aswar, Aswar; Rahmaliasari, Siti Heni (Adaptive Governance Research, 2024)
Purpose: This study aims to examine how adaptive governance enhances community resilience in responding to environmental change in South Sulawesi, Indonesia, by analyzing how local institutions, social networks, and knowledge systems interact to support collective adaptation strategies. Subjects and Methods: A qualitative research design was employed, involving in-depth interviews with community leaders, local government officials, and key stakeholders in both coastal and upland areas. Data collection was supported by direct field observations and document analysis to capture institutional practices, social interactions, and knowledge-sharing processes. The data were analyzed thematically to identify patterns and relationships that illustrate the mechanisms through which governance and community action contribute to resilience. Results: The findings show that institutional flexibility enables rapid, context-sensitive decision-making and supports the integration of traditional and formal governance structures. Social capital and collective action play vital roles in mobilizing community resources, building trust, and sustaining cooperation in addressing environmental challenges. Knowledge integration, combining local ecological insights with scientific understanding, promotes continuous learning and innovation in adaptation practices. Participatory governance also strengthens legitimacy and community engagement, enhancing the capacity to respond to complex socio-ecological dynamics. Conclusion: The study concludes that resilience in South Sulawesi is strengthened not through rigid control, but through flexibility, collaboration, and continuous learning within socio-ecological systems. Adaptive governance fosters inclusivity, reflexivity, and co-creation among institutions and communities. It positions managers as facilitators of collective intelligence, encouraging distributed leadership, trust-based networks, and equity-centered decision-making to support sustainable and just futures.